FOLLOW UP OF CHILDREN WITH KIDNEY INJURY IN NEONATAL AGE - Timovska, Silvana Naunova; Bojadzieva, Sonja; Mangjukovska, Hristina (Journal of Morphological Sciences, 2021)
Long-term follow-up of patients with acute kidney injury (AKI) has shown that glomerular filtration and tubular function are still normal. Renal blood flow remains permanently impaired, suggesting that there is still some irreversible loss of nephrons and that glomerular filtration is maintained by hypertrophy of the remaining nephrons. The aim of the study was to identify signs of  chronic kidney diseases in children with kidney injury in neonatal age. The study was designed as a prospective investigation conducted in the period of two years, which included 50 neonates with kidney injury hospitalized in NICU, University Clinic for Pediatric Diseases in Skopje. Due to the potential risk of developing chronic renal failure by the end of the first year of life, in 26 children with kidney injury in neonatal age were evaluated growth and development, arterial tension, and renal function. The material was statistically analyzed using methods of descriptive statistics. Of the total of 50 neonates with documented AKI, we followed 26 neonates because of the risk of disease progression to chronic renal failure. According to the results from the percentage growth curves, 85% of children had a normal finding, while 15% were obese children, with weighing between 85 and 95 percentiles. 96% of children had arterial tension with reference values â€‹â€‹according to age group, and only one child had prehypertension. We registered microproteinuria in 7.6% of children, and there were no hematuria findings. Most of the monitored children had proper renal function, which was probably due to the predominance of prerenal AKI, associated with a better prognosis. The follow-up period of one year was short and in order to obtain more reliable results, long-term controlled monitoring is required, which would last several years. Keywords:   neonates, acute kidney injury, follow-up  https://doi.org/10.55302/JMS2142174nt